Effect of the Variation of Pressure on the Dynamics and Neutron Yield of Plasma Focus Machines - Arwinder, Singh*; Lee, Sing*; Saw, S. H. (IEEE, 2017)
Data from the 2002 Imperial College plasma focus (ICpf) are used to study the dynamics of axial and radial phase as functions of pressure. The speeds are found to deviate from the ideal constant current electromagnetic rule of v ∼ P−n0 , (where n=0.5 ) with the modulus going below 0.5, due to the back-electromotive force varying the peak drive current even at fixed voltage operation. The amount of deviation depends on machine parameters and varies from a modulus of 0.3 for the NX1 axial phase to 0.47 in the INTI Plasma Focus (INTI PF) axial phase. The radial phase of the ICpf is characterized by a modulus of 0.48. The computed results are experimentally verified in the case of the NX1 and INTI PF axial phase. The effect on neutron yield is briefly discussed.